The Existence of Pesantren, Kiai and Kitab Kuning learning as the Main Element of Islamic Education in Indonesia - Zulmuqim, Zulmuqim (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2017)
The aim of Â this article was to discuss the existence of pesantren, kiai and kitab kuningis the main element of Islamic education in Indonesia. In pesantren carried out process to understand, live and practice the teachings of Islam, which emphasizes the importance of Islamic moral morality as a guide of daily life. Pesantren is led by a kiai. Kiai domiciled as a central figure in the lifestyle of pesantren, as well as owner and teacher. In addition, kiai is also a role model and a holder of absolute wisdom in the value of pesantren. Kiai teaches the science of Islam by using Yellow book. The Kitab kuning is an Arabic-speaking religious book, Malay, Javanese or any other language in Indonesia. Originally a kitab kuning written by Middle Eastern scholars such as Minhaj al-Thalibin by Abu Zakaria al-Nawawi (d667 H/1277 AD), the book of Kanz al-Raghibin by Jalal al-Din al-Mahalli (864 H/1460 M), the book Minhaj al-Thullab and Fath al-Wahhab by Zakariyya al-Ansari (w 926 H/1520 AD) and others. But there are also only titles using Arabic, but in Malay, like the Book of Jurisprudence or Fiqh Sirat al-Mustaqim by al-Raniri (d.1068 AH/1658 AD), the book of tasawuf akhlaqi Siyar alSalikin by Abd Shamad al-Falimbani (d.1832AD), the book of fiqh of Sabil alMuhtadin by Muhammad Arsyad al-Banjari (1812 AD). The three main components of Islamic education (pesantren, kiai and kitab kuning) to this day still exist and very meritorious in the development of Islamic education in all corners of Indonesia.